Reconstruction of Full Thickness Scalp Defects in Extremely Elderly Patients Using Dermal Regeneration Templates. Issue 5 (July 2020) - Bernstein, Jaime L.; Premaratne, Ishani D.; Levy, Adam S.; Kuhel, William I.; Kutler, David I.; Spector, Jason A.
Abstract : Abstract: The reconstruction of full thickness scalp defects following oncologic resection poses a unique challenge that is further magnified in "extremely elderly" patients, defined as those in at least their ninth decade of life, who are often unsuitable candidates for complex reconstruction. A "simpler" option is two-stage reconstruction: placement of Integra dermal regenerative template (Integra Life Science, Plainsboro, NJ) followed by a split thickness skin graft (STSG). This case series illustrates the success of this technique in the extremely elderly. A retrospective analysis of patients > 80 years at the time of surgery who underwent full thickness scalp reconstruction following tumor extirpation in a two-stage approach under the care of single surgeon from January 2010 to June 2019 was conducted. Variables reviewed were medical history, surgical treatment response, time to split thickness skin graft, follow up, and success of wound coverage. Fourteen patients, with a mean age of 87 years (range: 80 to 101, median: 87), met inclusion criteria. Split thickness skin grafts were placed after an average of 18 days. Twelve patients had successful two-stage reconstruction with 100% take. One patient developed a hematoma under a portion of the template that neither required reoperation nor delayed split thickness skin graft placement. A second suffered from insufficient vascularization of the template with delay to split thickness skin graft and incomplete wound closure. This two-stage approach is a successful primary reconstructive option for definitive management of full thickness scalp defects following oncologic resection in extremely elderly patients.